Consequences of the COVID-19 Pandemic on Children's Mental Health: A Meta-Analysis - Bussières, Eve-Line; Malboeuf-Hurtubise, Catherine; Meilleur, A.; Mastine, Trinity; Hérault, Elodie; Chadi, Nicholas; Montreuil, Marjorie; Généreux, Mélissa; Camden, Chantal; , PRISME-COVID Team; Camden, Chantal; Malboeuf-Hurtubise, Catherine; et al. (Frontiers in Psychiatry, 2021)
Background. The COVID-19 pandemic has exacerbated mental health problems in many individuals, including children. Children with pre-existing socio-demographic or developmental risk factors may be particularly vulnerable to the negative effects of the pandemic and associated public health preventive measures. Objective. This systematic review and meta-analysis explored the impacts of the COVID-19 pandemic on the mental health of children aged 5 to 13 years-old, while highlighting the specific difficulties experienced by children with neurodevelopmental issues or chronic health conditions. Methods. A systematic search of the published literature was conducted in Medline, ERIC, PsycINFO, and Google Scholar, followed by a quantitative meta-analysis of the eligible studies. Results. Out of the 985 articles identified, 28 empirical studies with prospective or retrospective longitudinal data were included in the quantitative synthesis. COVID-19 lockdown measures were associated with negative general mental health outcomes among children (g=0.28; p<.001; k=21), but of small magnitude. Sleep habits were also changed during the pandemic, as sleep duration significantly increased in children (g=0.32; p=.004, k=9). Moreover, results did not differ between children from the general population and those from clinical populations such as children with epilepsy, oncology, neurodevelopmental disorders, or obesity. Effect sizes were larger in European vs. Asian countries. Conclusions. Studies included in this review suggest that children’s mental health was generally negatively impacted during the COVID-19 pandemic. More research is needed to understand the long-term effects of the COVID-19 pandemic on children’s mental health and the influence of specific risks factors as they evolve over time.